Eventyrets tid, historiens rum: Trediveårskrigens dynamik i Den eventyrlige Simplicissimus - Overgaard, Mathias (Passage - Tidsskrift for litteratur og kritik, 2019)
Mathias Overgaard: “Fantastic Time, Historical Space – The Dynamics of the Thirty Years’ War in The Adventures of Simplicius Simplicissimus” This article sets out to investigate the presence of the Thirty Years’ War in Grimmelshausen’s Simplicissimus by illuminating the relationship between an ahistorical configuration of time and a historically specific spatiality. By analyzing the co-constitutional interrelation between Simplicius and the spaces he encounters, the article proposes a metaphysical reading of the protagonist as a disruptive element that resembles some of the changes which the war forced upon a great part of Europe.